The Influence of Work Environment, Work Discipline, Work Motivation, Leadership Style on Employee Performance with the Mediating Variable of Job Satisfaction in Manufacturing Company Employees in Batam - Tan, Cristina; Yuswardi, Yuswardi; Setyawan, Agustinus (Universitas Islam Kadiri, 2024)
This research aims to determine the impact of the work environment, work discipline, work motivation, and leadership style on employee performance, with a focus on the mediating role of job satisfaction. The quantitative analysis method was employed, involving the distribution of questionnaires to 400 respondents from manufacturing companies in the city of Batam. The findings of the study reveal several significant relationships. The work environment has a considerable effect on job satisfaction, and similarly, work discipline and work motivation also significantly influence job satisfaction. Leadership style is found to have a significant impact on job satisfaction. Importantly, job satisfaction is identified as a significant factor influencing employee performance. Furthermore, the study indicates that job satisfaction mediates the relationship between the work environment and employee performance. Similarly, work discipline, work motivation, and leadership style also exhibit a mediated impact on employee performance through job satisfaction. These research results provide insights into the factors contributing to the development of highly qualified employees. Moreover, the study emphasizes the pivotal role of employee performance, highlighting its substantial impact on the overall success and performance of a company.